The 3-Dimensional Grid: A Novel Approach to Stereoelectroencephalography. Issue 1 (16th January 2015) - Munyon, Charles; Sweet, Jennifer; Luders, Hans; Lhatoo, Samden; Miller, Jonathan
Abstract: BACKGROUND: Successful surgical treatment of epilepsy requires accurate definition of areas of ictal onset and eloquent brain. Although invasive monitoring can help, subdural grids cannot sample sulci or subcortical tissue; traditional stereoelectroencephalography depth electrodes are usually placed too far apart to provide sufficient resolution for mapping. OBJECTIVE: To report a strategy of depth electrode placement in a dense array to allow precise anatomic localization of epileptic and eloquent cortex. METHODS: Twenty patients with medically intractable epilepsy either poorly localized or found to arise adjacent to eloquent areas underwent placement of arrays of depth electrodes into and around the putative area of seizure onset with the use of framed stereotaxy. Each array consisted of a "grid" of parallel electrodes in a rectangular pattern with 1 cm between entry sites. In a subset of patients, a few electrodes were placed initially, with additional electrodes placed in a second stage. Trajectories were modified to avoid cortical vessels defined on magnetic resonance imaging. Patients were monitored for 4 to 21 days to establish the precise location of seizure onset. Stimulation was performed to map cortical and subcortical eloquent regions. Electrode locations were coregistered for frameless stereotaxy during subsequent resection of seizure focus. RESULTS: Two hundred fifty-four electrodes were implanted. Discrete regions of seizure onset and functional cortex were identified, which were used during resection to remove epileptogenic tissue while preserving eloquent areas. There were no hemorrhagic or infectious complications; no patient suffered permanent neurological deficit. CONCLUSION: The 3-dimensional intraparenchymal grid is useful for identifying the location and extent of epileptic and eloquent brain.